واقع القياس المحاسبي عن التكاليف البيئية في المؤسسات الاقتصادية الجزائرية - زعرور, نعيمة; سعدي, عبد الحق (جامعة الوادي University of Eloued, 2020)
هدف هذه الدراسة الى ابراز واقع القياس المحاسبي للتكاليف البيئية في المؤسسات الاقتصادية الجزائرية، وذلك من خلال عرض المفاهيم المتعلقة بالقياس المحاسبي للتكاليف البيئية في الاطار النظري، وذلك بالاعتماد على المنهج الوصفي، ولتحقيق اهداف الدراسة تم الاعتماد على أسلوب دراسة حالة في مؤسسة البسكرية للاسمنت، حيث توصلت هذه الدراسة الى أن المؤسسة تقوم بقياس بعض التكاليف البيئية والإفصاح عنها، ولكن بشكل غير منفصل عن باقي التكاليف الأخرى، وان هناك بطء في استجابة الفكر المحاسبي والتطبيق العملي فيما يتعلق بإدخال تحسينات على النظم المحاسبية لتصبح أكثر قدرة على استيعاب التكاليف البيئية. This study aims to highlight the reality of accounting measurement of environmental costs in Algerian economic institutions, by presenting the concepts related to accounting measurement of environmental costs in the theoretical framework, based on the descriptive approach, and to achieve the objectives of the study was based on the method of A case study at Al-Biskria Cement, where this study found that the institution measures some environmental costs and discloses them, but not separately from other costs, and that there is a slow response to accounting thought and practical application with regard to improvements to accounting systems to become more able to absorb environmental costs.
The reality of accounting of environmental costs in Algerian economic entreprises Case Study: Al-Baskria Cement Foundation
مقال
Keywords: محاسبة البيئية، تكاليف بيئية، قياس محاسبي، قياس محاسبي عن تكاليف البيئية.; Environmental accounting ;environmental costs; accounting measurement; accounting measurement of environmental costs.